(untitled) (World Bulletin of Management and Law, 2024)
This article examines the social relations developing in the field of the realization of the electoral rights of citizens of the Republic of Uzbekistan during elections. It is the exercise of citizens’ electoral rights that ensures the sovereignty of the people, a democratic, political regime and control over the political elite by the population